Enteropathogenic (EPEC) and Shigatoxigenic Escherichia coli (STEC) in broiler chickens and derived products at different retail stores - Alonso, Mónica Zulema (2012)
Enteropathogenic (EPEC) and Shigatoxigenic Escherichia coli (STEC) are foodborne pathogens that cause potentially fatal infant diarrhea and hemolytic uremic syndrome, respectively. We investigated the presence of intimin and Shiga toxin encoding genes, as indicators of EPEC and STEC presence in cloacae and chicken products. The analyzed products were hamburgers, giblets and carcasses obtained from poultry and butcher shops. EPEC contamination predominated over STEC contamination in cloacae and chicken products, although some differences were detected when the kind of food or shop was taken into account. In particular, among chicken hamburgers we found a greater proportion of EPEC than STEC-positive samples at poultry shops, while in butcheries STEC was predominant. This finding could suggest cross contamination during handling at butcheries. The results indicate that it is necessary to improve hygienic measures both during slaughtering and manipulation of chicken products at retail stores, to provide a safe product to consumers.